2012
DOI: 10.1111/j.1654-1103.2012.01401.x
|View full text |Cite
|
Sign up to set email alerts
|

Scale dependence of vegetation–environment relationships: a meta‐analysis of multivariate data

Abstract: Questions How does spatial scale (extent and grain) influence the relative importance of different environmental factors as determinants of plant community composition? Are there general scale thresholds that mark the transition from primarily edaphic to primarily climatic control of plant communities? Location Global. Methods We surveyed the empirical literature and identified 89 analyses from 63 published studies that analysed vegetation–environment relationships involving at least two categories of predicto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
82
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 30 publications
12
82
4
2
Order By: Relevance
“…There is partial agreement, too, with the findings reported by Siefert et al (2012), who studied the influence of spatial scale on the relative importance of climate or soils in determining the floristic composition of plant communities. From 89 analyses derived from 63 different studies, they concluded that there is a transition from a primarily edaphic influence to a primarily climate-related influence as the spatial scale increases.…”
Section: Vegetation Typessupporting
confidence: 77%
“…There is partial agreement, too, with the findings reported by Siefert et al (2012), who studied the influence of spatial scale on the relative importance of climate or soils in determining the floristic composition of plant communities. From 89 analyses derived from 63 different studies, they concluded that there is a transition from a primarily edaphic influence to a primarily climate-related influence as the spatial scale increases.…”
Section: Vegetation Typessupporting
confidence: 77%
“…It has long been recognized that besides climate, the edaphic factor chiefly drives the geographic distribution of plant species (Good, 1931). A recent meta-analysis by Siefert et al (2012) corroborates an oft-held view among ecologists and geographers that climate strongly influences the vegetation-environment relationship at larger scales while edaphic factors are relatively more important at smaller spatial scales.…”
mentioning
confidence: 69%
“…The three major principles of CAS theory discussed in this article (complex interaction, adaptation and scale dependence) are subject to major interest and intensive research efforts in ecology and biogeography (e.g., Levin 1992, Pearson and Dawson 2003, Folke 2006, Siefert et al 2012. However interactions between these principles in affecting ecosystem dynamics have rarely been tackled.…”
Section: Discussionmentioning
confidence: 99%